PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, TIPE AUDITOR DAN TIPE INDUSTRI TERHADAP PENGUNGKAPAN MODAL INTELEKTUAL (Studi Empiris Pada Perusahaan yang Termasuk Dalam Indeks Kompas 100 Tahun 2014 Bursa Efek Indonesia) - Rima Aprisa; Amries Rusli Tanjung; Alfiati Silfi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This study aims to examines the influence of firm size, profitability, auditor type and industry type to the intellectual capital disclosure. The sampel used is secondary data from the Indonesia Sock Exchange (IDX) by using annual report of 100 companies that listed in index kompas 100 in 2014. The method of determining the sample is by using purposive sampling method, while the data processing method used in this study is the multiple regression analysis. The result of this study indicates: (1) firm size has a significant influence toward the intellectual capital disclosure with significance value 0,022, (2) auditor type has a significant influence toward the intellectual capital disclosure with significance value 0,000, (3) industry type has a significant influence toward the intellectual capital disclosure with significance value 0,004, (4) but profitability does not have a significant influence toward intellectual capital disclosure.Keywords: intellectual capital disclosure, firm size, profitability, auditor type, and industri type.